Draft Annual Plan 1986-87 Volume-I An Overview Government of Assam - Planning Commission (Planning Commission, 1986)
Assam occupies a position of strategic importance in the North-Eastern Region, because of her peculiar geographical location. The entire region is connected with the rest of the country by a slender corridor leading from Dhubri and Kokrajhar districts of Assam. She serves as a gateway to the neighbouring States of Manipur, Meghalaya, Nagaland and two Union Territories of Mizoram and Arunachal Pradesh.
Planning and Development Department, Government of Assam